Neuropedagogy and alternative education in the 21st-century education - Małgorzata Chojak (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The article attempts to outline the similarities and differences between neuropedagogy and alternative education - as concepts, which are the modern answer to the failure of the current education system. Praised by some, they are heavily criticized by others. For some, they are the ideal solution, which supports the development of children, for which there is no place in a traditional school, for others - a way of living the good life and a source of income. Regardless of the evaluation, it is worth taking a closer look at their sources, the proposed original solutions and the impact on the traditional system of education.